2019
DOI: 10.1183/13993003.00804-2019
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality in patients with corticosteroid-dependent asthma: a nationwide population-based study

Abstract: IntroductionChronic systemic corticosteroid (CS) therapy is associated with an increased risk of mortality in patients with many chronic diseases. However, it has not been elucidated whether chronic systemic CS therapy is associated with increased mortality in patients with asthma. The aim of this study was to determine the effects of chronic systemic CS therapy on long-term mortality in adult patients with asthma.MethodsA population-based matched cohort study of males and females aged ≥18 years with asthma wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 34 publications
2
67
0
3
Order By: Relevance
“… 5 7 Patients with CS-dependent asthma show an increased use of healthcare resources and higher mortality than other patients with asthma. 8 Because it causes a substantial burden on public health, 9 11 identifying and modifying factors associated with poor outcomes in patients with CS-dependent asthma may be the cornerstone to improving treatment outcomes in this population.…”
Section: Introductionmentioning
confidence: 99%
“… 5 7 Patients with CS-dependent asthma show an increased use of healthcare resources and higher mortality than other patients with asthma. 8 Because it causes a substantial burden on public health, 9 11 identifying and modifying factors associated with poor outcomes in patients with CS-dependent asthma may be the cornerstone to improving treatment outcomes in this population.…”
Section: Introductionmentioning
confidence: 99%
“… 21 A population-based matched cohort study from Korea revealed that long-term use of SCS was associated with an increased mortality risk in a dose-dependent manner in patients with asthma. 22 Moreover, quantitative studies reported that exacerbation of asthma and long-term OCS-use negatively impacted professional life and made maintaining a normal life challenging. 23 …”
Section: Definition Prevalence and Burden Of Samentioning
confidence: 99%
“…However, chronic OCS use has serious side-effects. Moreover, CS-dependent asthma is associated with an increased risk of mortality 22 ; therefore, CS should be considered as the last controller.…”
Section: Treatment Of Samentioning
confidence: 99%
“…In this issue of the European Respiratory Journal, LEE et al [4] examine more than 8000 cases of SCS-dependent asthma and report that chronic SCS use is associated with increased risk of mortality (hazard ratio 2.17). They also report that there is a significant dose-response relationship; that is, the higher the dose of steroids, the higher the risk.…”
mentioning
confidence: 99%
“…They also report that there is a significant dose-response relationship; that is, the higher the dose of steroids, the higher the risk. LEE et al [4] performed a population-based matched cohort study using the Korean National Health Insurance Service database from 2005 to 2015. The importance of the study comes with the enormous database, a total of 466 941 patients with asthma, of whom 8334 were SCS-dependent.…”
mentioning
confidence: 99%